Complexity of semi-algebraic proofs - Grigoriev, Dima (2013)
Proof systems for polynomial inequalities in 0-1 variables include the well-studied Cutting Planes proof system (CP) and the Lovász- Schrijver calculi (LS) utilizing linear, respectively, quadratic, inequalities. We introduce generalizations LSd of LS involving polynomial inequalities of degree at most d.